Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Connect with a community of experts ready to provide precise solutions to your questions quickly and accurately. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Answer:
Step-by-step explanation:
Equation
3x + 9 + 2x = x - 2x - 3
Solution
Combine all the like terms.
3x+2x+9 = x - 2x - 3
5x + 9 = -x - 3 Add x to both sides of the equation
5x+x +9 = -x+x -3 Combine
6x + 9 = - 3 Subtract 9 from both sides of the equation
6x+9-9 = - 3-9 Combine
6x = -12 Divide both sides by 6
6x/6 = -12/6
x = - 2
Answer x = - 2
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.